Lake Superior Paper - Blast-Furnace Plant of the "Elba" Società Anonima di Miniere è di Alti Fòrni at Portoferraio, Elba. - Carlo Massa (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
The Societâ Anonima di Miniere e di Alti Fòrni, familiarly known as the " Elba Company," works the rich ore-deposits of the Island of Elba under a long-term contract with the Italian Government. The ore-deposits are scattered over the eastern and southeastern coast; but as these parts of the island are not well provided with ports, the blast-furnaces were built at Porto-ferraio, the principal town of the island, situated on the northern shore, and possessing a magnificent natural harbor where vessels even as large as the battleships of the Italian navy can comfortably anchor. In the selection of Portoferraio the cost of transporting the iron-ore from the different mines to the blast-furnaces has been reduced to a minimum, and shelter has been provided for the company's flotilla of tugs and barges, as well as for the steamers carrjing coal and pig-iron. The whole plant, of which a general view is given in Fig. 1, comprises: 1. A discharging-pier with unloading-cranes. The ore and coal are transported from this pier by means of an aerial cable-railway to the coal- and ore-storage yards. This cable-railway is supported by an iron bridge extending from the pier to the shore and by a wooden trestle extending from the shore to the yards. 2. Blast-furnaces, two in number, with all the accessory apparatus, such as blowing-engines, dry purifiers, Cowper hot-blast stoves, hoists, etc. 3. Coke-ovens, two batteries, with coal-bin, crushers and boilers. 4. Engine-house containing the blast-engines and the electric generating-station. 5. Pumping-plant. 6. Narrow-gauge railways.